The prevalence and predictors of herb-drug interactions among Iranian cancer patients during chemotherapy courses - Maliheh Sadat Bazrafshani; Abbas Pardakhty; Behjat Kalantari Khandani; Haleh Tajadini; Sadra Ghazanfari Pour; Sara Hashemi; Shiva Amiri; Soheil Mehmandoost; Amin Beigzadeh; Samaneh Abbaszadeh; Hamid Sharifi (BMC, 2023)
Abstract Background The concurrent usage of herbal medicines with conventional therapies is an important concern in cancer treatment which can lead to unexpected consequences like herb-drug interactions. This study aimed to determine the prevalence of potential herb-drug interactions and to predict factors associated with herb-drug interactions for cancer patients. Methods This cross-sectional study was conducted among a convenience sample of 315 cancer patients referring to the oncology clinics of Kerman city in 2018. Data were collected via comprehensive face-to-face interviews and medical chart reviews. A drug interaction checker was used to determine herb-drug interactions. The information of patients was compared based on herb-drug interactions using bivariable logistic regression models, and predictors were determined by the multivariable logistic regression model. All analyses were performed by Stata software version 16. Results Of 262 patients (83.2% of the patients) who used herbal medicines, 209 patients [79.8% (95% Confidence Intervals (CI): 75.2 - 85.1)] had potential herb-drug interactions. Chamomile was the most popular herbal medicine (n = 163, 78.0%), and minor and moderate herb-drug interactions were caused by green tea (n = 34, 16.3%) and peppermint (n = 78, 37.5%). The number of chemotherapeutic agents (OR: 1.92, 95% CI: 1.43-2.58; P-value < 0.0001) and the experienced of pain during chemotherapy courses (OR = 2.22, 95%CI:1.00-4.94; P-value = 0.04) were some of the predictors of herb-drug interactions among cancer patients. Conclusion Herbal medicine use during chemotherapy was found prevalent among cancer patients; of them, the experience of potential herb-drug interactions was highly frequent. Oncologists and clinical pharmacologists are recommended to take into account challenges associated with herb-drug interactions in their routine practices, particularly during chemotherapy among these patients.